Women and Domestic Violence in Bone, South Sulawesi: Sociological Perspectives, Legal Awareness, and Gender - Abidin, Kurniati; Latif, Hamzah; Faturrahman, Faturrahman; Azzahrah, Waode Mabrukah; Makkarateng, Ma’adul Yaqien (Samarah: Jurnal Hukum Keluarga dan Hukum Islam, 2026)
Domestic violence remains a social problem affecting many women in Indonesia, reflecting gender inequality rooted in social and legal structures. This study aims to understand the decision-making process of female victims of domestic violence who choose not to report their experiences. The study employed empirical legal methods, analyzed using theories of legal sociology, legal awareness, and gender. Data were collected through observation, interviews, and document studies. The informants interviewed included female victims, victims of violence, academics, and religious leaders. The data analyzed consisted of primary and secondary data. The results show that the decision to remain silent is not merely a result of fear or powerlessness, but rather a form of rational, reflective agency within limitations. This decision is formed through the accumulation of social factors, patriarchal culture, and unequal gender power relations in society, which place women in a subordinate position. Furthermore, the meaning of law for female victims is understood as a masculine social force and is far from their lived experiences, so that formal law loses its relevance in providing protection. The solution offered is that concrete steps are needed in the future from the government and related institutions, religious leaders, and communities to provide legal protection, build awareness, and provide equal education so that women can obtain justice. These findings enrich sociological, legal and gender awareness studies by showing that the experiences of female victims of domestic violence are a real struggle in facing an unjust social system.